SOSIALISASI DAN IMPLEMENTASI DESAIN BESAR OLAHRAGA DAERAH (DBOD) KEOLAHRAGAAN KABUPATEN CIANJUR - Rahadian, Adi; Afriyuandi, Asep Ramdan; Pratama, Andi Kurniawan; Sungkawa, Muhamad Guntur Gaos; Amalia, Eneng Fitri; Adriyan, Adriyan; Ramdani, Muhammad Rafly; Erlangga, Ariel; Julianto, Fadli Rahman; Fadilah, Tiar; Rustandi, Beny (MAJU : Indonesian Journal of Community Empowerment, 2025)
The socialization and implementation of the Desain Besar Olahraga Daerah (DBOD) is a strategic step in supporting structured, sustainable, and locally-based sports development. Cianjur City, as part of West Java Province, has the potential of human resources, culture, and geography that support sports development at both the participatory and achievement levels. However, challenges remain in sports governance, limited infrastructure, low synergy among stakeholders, and the absence of a comprehensive long-term planning document. Through this activity, it is hoped that a shared understanding of the direction and objectives of the DBOD will be created, while also encouraging the active involvement of local governments, educational institutions, sports organizations, and the community. The main objectives of this activity are to socialize the concept and content of the DBOD, increase stakeholder capacity, and formulate implementation strategies that are appropriate to regional characteristics. The results of this activity are expected to strengthen the regional sports ecosystem and serve as a reference in the planning, implementation, and evaluation of sports programs in Cianjur City in a sustainable.